Past and future of an IMI-PharmaTrain (IMI-PhT)-initiated multinational pharmaceutical medicine course at the Semmelweis University in Hungary - Kerpel-Fronius, S.; Gottwald, M.; Arányi, P.; Renczes, G.; Görbe, A.; Papp, R.; Ferdinandy, P. (Frontiers in Pharmacology, 2024)
The pharmaceutical medicine course at the Semmelweis University of Budapest, Hungary was initiated as part of the Innovative Medicines Initiative (IMI) Pharmaceutical Medicine Training Programs (16 IMI Call 2008/1/16). The aim was to extend training of pharmaceutical medicines development to those EU Member States where no such education was present. The final program envisaged the development of a cooperative education supported by universities located in Central-Eastern Europe. It was considered to be the economically and scientifically most viable approach to combine the expertise from these countries to form a united teaching staff and provide education jointly for the young professionals of the region. Semmelweis University was selected to manage this coordinated program. In this report, we describe the organization and functioning of this international university-based pharmaceutical medicine education project called Cooperative European Medicine Development Course (CEMDC) and evaluate its successes and shortcomings. During the pandemics, the education was interrupted. The follow-on program is reorganized as a postgraduate MSc course named "Semmelweis Pharma MBA" and will be started in 2025. It will continue the established PharmaTrain educational tradition. However, it will deal in more detail with the transition from basic pharmacological to industrial research, as well as biopharmaceutical formulation, manufacturing and marketing aspects of medicines development.